Factors that influence value creation and value capture in companies – evidence in an emerging market - Montoya Ramírez, Manuel Fernando (2025)
The objective of this study is to analyze the influence of the following variables – technological innovation, creativity and innovation management and business model innovation – on two variables: value creation in companies and value capture in companies.